Role of ATP in Extracellular Vesicle Biogenesis and Dynamics - Lombardi, Marta; Gabrielli, Martina; Adinolfi, Elena; Verderio, Claudia (Frontiers in Pharmacology, 2021)
Adenosine triphosphate (ATP) is among the molecules involved in the immune response. It acts as danger signal that promotes inflammation by activating both P2X and P2Y purinergic receptors expressed in immune cells, including microglia, and tumor cells. One of the most important receptors implicated in ATP-induced inflammation is P2X7 receptor (P2X7R). The stimulation of P2X7R by high concentration of ATP results in cell proliferation, inflammasome activation and shedding of extracellular vesicles (EVs). EVs are membrane structures released by all cells, which contain a selection of donor cell components, including proteins, lipids, RNA and ATP itself, and are able to transfer these molecules to target cells. ATP stimulation not only promotes EV production from microglia but also influences EV composition and signaling to the environment. In the present review, we will discuss the current knowledge on the role of ATP in the biogenesis and dynamics of EVs, which exert important functions in physiology and pathophysiology.